Deutsche Arbeitsmarktregionen – Neuabgrenzung nach den Kreisgebietsreformen 2007–2011 - Kosfeld, Reinhold; Werner, Alexander (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
Studies in Regional Economics require functional regions as statistical units. Regional labour markets are characterized by close commuter links in the regional labour markets and high seclusion towards other regional labour markets. From time to time a new delineation of regional labour markets is necessary, due to permanent changes in both, the economic and the commuter structure of a country. Particularly in Germany a new delineation is necessary, because in recent years reforms of the area of the German districts change the basis for the regional labour markets. Former delineations cannot be reconstructed with the new district boundaries. As a method to construct new regional labour markets in Germany we employ the factor analysis with oblique Oblimin rotation to German commuter structure. Additionally, the commuting distance is considered as a constraint, which improves the homogeneity of the regional labour markets, and within commuting distance of employment areas is limited to politically acceptable commuting distances. Hereby we delineate 141 regional labour markets in Germany.
Keywords: Regional delineation; Labour market regions; Factor analysis